Perovskite-molecule composite thin films for efficient and stable light-emitting diodes - Heyong Wang (Nature Portfolio, 2020)
The field of perovskite light-emitting diodes witnesses rapid development in both device processing strategies and performances. Here Wang et al. develop high-quality perovskite-molecule composite thin films and achieve high quantum efficiency of 17.3% and half-lifetime of 100 h.